Conventional and new-breeding technologies for improving disease resistance in lentil (Lens culinaris Medik) - Roy, Anirban; Sahu, Parmeshwar K.; Das, Camellia; Bhattacharyya, Somnath; Raina, Aamir; Mondal, Suvendu (Frontiers in Plant Science, 2023)
Lentil, an important cool season food legume, is a rich source of easily digestible protein, folic acid, bio-available iron and zinc nutrients. Lentil is growing mainly as a sole crop in winter season after harvesting rice in South Asia. However, the annual productivity is low due to its slow growth during early phase, competitive weed infestation, and disease outbreaks during the crop growth period. Disease resistance breeding has been practiced for a long time to enhance resistance against various diseases. Often the sources of resistance are available in wild crop relatives. Thus, wide hybridization and the ovule rescue technique have helped to introgress the resistance trait into cultivated lentil. Besides hybridization, induced mutagenesis contributed immensely in the creation of variability for disease tolerance, and several disease-resistant mutant lines have been developed. However to overcome the limitations of traditional breeding approaches, advancement in molecular marker technologies, genomics and new breeding technologies has helped in developing disease-resistant and climate-resilient lentil varieties with more precision and efficiency. This review describes biotic constraints, disease screening methods, and the role of the conventional and new breeding technologies in alleviating disease incurred damage and progress toward making lentil varieties more resilient to the disease outbreaks under the shadow of climate change.